Pneumococcal pneumonia complicating secondary bacteremia in an immunocompromised patient: a case report - Datta, Sangeeta; Kumar, Avinash; Sinha, Manish Kumar; Chatarjee, Biswaroop (International Journal of Research in Medical Sciences, 2024)
Pneumococcal pneumonia is a significant global public health issue, contributing to considerable morbidity and mortality, as well as placing a strain on healthcare systems. Here, we present the case of a 46-year-old female who was admitted to our hospital with a sudden onset of shortness of breath and right-sided substernal chest pain on the day of admission, accompanied by fever and a productive cough. She displayed an increased respiratory rate and diminished vesicular breath sounds, with bilateral scattered rhonchi. Blood tests and chest radiological findings suggested an infectious etiology. Ultimately, Streptococcus pneumoniae was isolated through microbiological culture from both sputum and blood samples, showing similar antimicrobial sensitivity, and appropriate management was initiated. She was discharged after five days of hospitalization, with an uneventful recovery. Appropriate antimicrobial stewardship and pneumococcal vaccination are essential to combat this infection.